2020
DOI: 10.1186/s12967-020-02618-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophage, angiogenesis and lymphangiogenesis markers predict prognosis of non-small cell lung cancer patients

Abstract: Background The tumor microenvironment (TME) is a critical player in tumor progression, metastasis and therapy outcomes. Tumor-associated macrophages (TAMs) are a well-recognized core element of the TME and generally characterized as M2-like macrophages. TAMs are believed to contribute to tumor progression, but the mechanism behind this remains unclear. We aimed to investigate the clinical, angiogenic, and lymphangiogenic significance of TAMs in non-small cell lung cancer (NSCLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 63 publications
9
122
0
Order By: Relevance
“…CD68 is a major biomarker for the quantification of tumor-associated macrophages (TAMs) (48). As we all know, TAMs are a wellrecognized core element of tumor microenvironment (TME) and generally characterized as M2-like macrophages which are associated with tumor progression and poor prognosis (49,50). This is the reason that high tumor CD15 and CD68 expression indicates a limited response and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…CD68 is a major biomarker for the quantification of tumor-associated macrophages (TAMs) (48). As we all know, TAMs are a wellrecognized core element of tumor microenvironment (TME) and generally characterized as M2-like macrophages which are associated with tumor progression and poor prognosis (49,50). This is the reason that high tumor CD15 and CD68 expression indicates a limited response and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…A negative control was produced by replacing the primary antibody with a phosphate buffer solution, and a positive control was generated using human testis tissues according to a previous report. 14 …”
Section: Methodsmentioning
confidence: 99%
“…11,12 Furthermore, for patients with colon cancer and non-small cell lung cancer, the inclusion of the CD163+/CD68+ ratio was found to significantly improve the accuracy of traditional tumor-node metastasis staging in predicting patient outcomes. 13,14 Previous studies have demonstrated that many factors can affect CB prognosis. For example, it has been reported that CB lesions located in the pelvis and proximal humerus have a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the tumor-associated macrophages resemble M2-like macrophages. Unlike M1-like macrophages with pro-inflammatory and anti-cancer activities, the M2-like macrophages function as immunosuppressive cells contributing to tumor initiation, angiogenesis, drug resistance, and metastasis [ 147 , 148 ]. The M2 macrophages help the immunosuppressive microenvironment by releasing anti-inflammatory cytokines, such as IL-20, TGF-β, and HGF [ 149 ], or by preventing the release of intracellular antigens from apoptotic cancer cells via efferocytosis [ 150 ].…”
Section: The Role Of Mertk In Egfr-tki Resistancementioning
confidence: 99%